Let be a linear transformation. Then there is a theorem that:

RankT + nullity T = n

This theorem is said to be equivalent to:

dim(Ran(T))+ dim(Kernel(T))= n

[n is the dimension of domain]

So here's my question: how can we use the first one to derive/prove the second?

This is my unsuccessful attempt:

And for nullity(T):nullity(T) = dim(null(T))

Since null(T) = ker(T)

So, nullity(T) = dim(ker(T))

For rank(T):rank(T) = dim(row(A))

Since row(A) = null(A) and null(A) = ker(T)

dim(row(A)) = dim(ker(T))

???

(Headbang)

I will be great if anyone could show me how to prove this. Thanks.